1979
DOI: 10.1017/s0033291700031937
|View full text |Cite
|
Sign up to set email alerts
|

The scientific status of electro-convulsive therapy

Abstract: Electro-convulsive therapy (ECT) has been available for just over 40 years, whereas neuroleptic drugs have recently celebrated their 25th anniversary. Yet much more is known of the magnitude and scope of effectiveness, the mechanism of action, and even the adverse effects, of neuroleptic drugs in the treatment of schizophrenia than of electro-convulsive therapy in depression. Research on drug therapy of schizophrenia has advanced rapidly in the past 15 years while clinical research on ECT has progressed little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The size of this trial, however, was totally inadequate to demonstrate any significant treatment differences. Methodological criticisms of other early trials of ECT can be found in Crow (1979). Unfortunately, inconsistent trial results and methodological criticisms of the early clinical trials enabled influential authors such as Sargant & Slater (1944 to continue to advocate the use of physical treatments on the basis of anecdotal evidence and personal prejudices.…”
Section: Early Evaluation Of Electroconvulsive Therapymentioning
confidence: 99%
“…The size of this trial, however, was totally inadequate to demonstrate any significant treatment differences. Methodological criticisms of other early trials of ECT can be found in Crow (1979). Unfortunately, inconsistent trial results and methodological criticisms of the early clinical trials enabled influential authors such as Sargant & Slater (1944 to continue to advocate the use of physical treatments on the basis of anecdotal evidence and personal prejudices.…”
Section: Early Evaluation Of Electroconvulsive Therapymentioning
confidence: 99%
“…The size of this trial, however, was totally inadequate to demonstrate any significant treatment differences. Methodological criticisms of other early trials of ECT can be found in Crow (1979). Unfortunately, inconsistent trial results and methodological criticisms of the early clinical trials enabled influential researchers such as Sargant andSlater (1944, 1963) to continue to advocate the use of physical treatments on the basis of anecdotal evidence and personal prejudices.…”
Section: Early Evaluation Oj Electroconvulsive Therapymentioning
confidence: 99%
“…Much of the available neuropharmacological data lacks anatomical detail and similar changes have not been demonstrated in humans. Little interest has focused on sub-convulsive stimulation of the brain, for it is accepted (Cronholm and Ottosson, 1960)-albeit on the basis of equivocal evidence (Crow, 1979;Deakin, 1983;Royal College of Psychiatrists, 1977)-that sub-convulsive ECT has no therapeutic benefit. Animal studies of subconvulsive ECS have demonstrated no neuropharmacological changes.…”
Section: Introductionmentioning
confidence: 99%